Nutrient-adequate diets with the lowest greenhouse gas emissions or price are the least acceptable—insights from dietary optimisation modelling using the iOTA model® - Tavan, Mahya; Smith, Nick W.; Fletcher, Andrew J.; Hill, Jeremy P.; McNabb, Warren C. (Frontiers in Nutrition, 2025)
Over the past decade, there has been an increasing interest in the environmental sustainability of diets because food systems are responsible for a third of the anthropogenic greenhouse gas emissions (GHGE). However, less attention has been paid to the nutrient adequacy, consumer acceptability, and affordability of such diets. Such knowledge is particularly scarce in New Zealand, where approximately 40% of adults and 20% of children may live under severe to moderate food insecurity. The iOTA Model® is a country-specific dietary optimisation tool designed to fill this gap by bringing the various aspects of diet sustainability together and providing evidence-based knowledge on not just the environmental impact of food but also its economic and nutritional sustainability. The iOTA Model® was constructed using mixed integer linear programming by integrating New Zealand-specific dietary data. Features such as digestibility and bioavailability considerations have been incorporated as part of the iOTA Model®, allowing for a more accurate estimation of nutrient supply. The model is available as an open-access tool and allows users to explore various dimensions of a sustainable diet. Eight optimisation scenarios, along with baseline diets, were investigated for adult males and females in New Zealand. Results showed that reducing dietary GHGE or price by approximately 80% was possible while meeting nutrient adequacy requirements. However, such diets deviated substantially from the baseline eating patterns, indicating lower consumer acceptability, and only included a limited variety of foods. On the contrary, diets with minimum deviation from baseline remained realistic while adhering to nutrient targets and reducing GHGE by 10 and 30% in female and male consumers aged 19–30 years, respectively, and weekly price remained below the baseline. Expansion of the model to additional countries and its open-access nature will allow independent dietary sustainability research through optimisation.